PERAN KOMUNIKASI DALAM MENGELOLA LEMBAGA PENDIDIDKAN - Ahmad Hariyadi (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2015)
Leader of education institution that can not communicate what they want, cannot able to bring education institution to the objective that they hope. A teacher that cannot able to communicate the knowledge that must be delivered to student well also cannot be able to give output or education result well. Thus it need some good communication in order that education institution can proceed well too. Communication is a process of changing and delivering information and idea from someone to the others. Other definition explain communication as some process and delivering message transaction from certain party, through certain medium, in the certain form, so can get the target, that is other party that cause certain relationship. In related with leadership, communication can be mean as process and delivering message transaction in two direction, that is from the leader to the member that led, and the opposite every componen in the education institution should can communicate what they hope so the organization can proceed more normally.